EFL Reading Comprehension Difficulties in Online Learning - Fadlullah; Marisa Yoestara; Septhia Irnanda (Universitas Serambi Mekkah, 2024)
This study aims to identify both linguistic and non-linguistic reading comprehension problems during online learning. This qualitative study used a descriptive design focusing on 18 of the fifth and seventh semester students from the English Education Department in the Teacher Training and Education Faculty in Serambi Mekah University. The instrument used in this study was a questionnaire. The data was analyzed by using qualitative analysis to explore the students’ reading comprehension difficulties during online learning. The results indicated that the students experienced the most reading problems in the areas of facilities (69.46%). This means the participants considered it as the most frequent problems that interfered with their reading comprehension during online learning.